SDSA: An Implementation of Secure Data Sharing Approach Using Homomorphic Encryption - Aaliya, T; Sharma, R (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is fast growing technology that enables the users to store and access their data remotely. While accessing the data from cloud, different users may have relationship among them depending on some attributes, and thus sharing of data along with user privacy and data security becomes important to get effective result. In this paper, we design and implement Secure Data Sharing Approach i.e. SDSA, for dynamic groups in public cloud environment. In this technique, user uploaded their data on cryptographic server in encrypted format using Homomorphic encryption algorithm tiger hash algorithm is used for key generation which is input in the encryption algorithm. In SDSA a user is able to share data with others in the group without revealing characteristics privacy to the other user. Moreover, SDSA supports efficient user revocation and fresh user joining. More especially, efficient user revocation can be achieved through a public revocation list without harming security of the other remaining users in user portal. In addition, the storage overhead and the encryption decryption computation cost are constant. Extensive analyses show that this proposed scheme satisfies the desired security requirements along with the secure sharing with other and preserve privacy policy when group sharing is processed that guarantees efficiency as well.